2014
DOI: 10.1016/j.surfrep.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and surface functionalization of silica nanoparticles for nanomedicine

Abstract: There are a wide variety of silica nanoformulations being investigated for biomedical applications. Silica nanoparticles can be produced using a wide variety of synthetic techniques with precise control over their physical and chemical characteristics. Inorganic nanoformulations are often criticized or neglected for their poor tolerance; however, extensive studies into silica nanoparticle biodistributions and toxicology have shown that silica nanoparticles may be well tolerated, and in some case are excreted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
255
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(273 citation statements)
references
References 123 publications
5
255
0
2
Order By: Relevance
“…S4 shows the effect of the accumulation of water molecules in the silica inner layer). It has additionally been proposed that systems with an excessive payload of Gd(III) may lead to a disproportionate weight of T 2 effects, which would have a negative effect on T 1 -weighted images (8,25,27,28). We did observe an increase in T 2 relaxivity by increasing the number of Gd(III) per nanoparticle.…”
Section: Significancesupporting
confidence: 48%
See 1 more Smart Citation
“…S4 shows the effect of the accumulation of water molecules in the silica inner layer). It has additionally been proposed that systems with an excessive payload of Gd(III) may lead to a disproportionate weight of T 2 effects, which would have a negative effect on T 1 -weighted images (8,25,27,28). We did observe an increase in T 2 relaxivity by increasing the number of Gd(III) per nanoparticle.…”
Section: Significancesupporting
confidence: 48%
“…A simple addition of APTES-SCN-DOTA (Fig. S1B) solution in ethanol during the silica growth process results in a different network structure with more defect sites compared with the TEOS network alone, which is more resistant to the etching process of Gd(NO 3 ) 3 (25)(26)(27). The difference in the particle's surface functionality and porosity can be examined by TEM ( Fig.…”
Section: Significancementioning
confidence: 99%
“…Furthermore, it has been demonstrated that the mesopores of these nanoparticles can be closed by APTES + PCL, GPTMS + CS, and their surfaces with the same organic matrices capping. As reported by Liberman et al [30], the presence of organic moieties in the surface increased the shapes and sizes of nanoparticles. It is worth mentioning that the MCM-41 is within the size expected to be used in biological applications.…”
Section: Scanning Electron Microscopy-semsupporting
confidence: 57%
“…[86][87][88] Hence, surface modi¯-cation methods have been used aiming to improve the colloidal stability of SNP in biological systems and increase circulation times, as well as to reduce overall toxicity and aggregation. 89 Bare colloidal SNP have the surfaces negatively charged at physiological pH due to the ionization of the hydroxyl groups (−OH).…”
Section: Snps Surface Functionalizationmentioning
confidence: 99%